2016
DOI: 10.1021/acs.biomac.6b00528
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Supramolecular Peptide–Poly(ethylene glycol) Hydrogels by Coiled Coil Self-Assembly and Self-Sorting

Abstract: Physical hydrogels are extensively used in a wide range of biomedical applications. However, different applications require hydrogels with different mechanical and structural properties.Tailoring these properties demands exquisite control over the supramolecular interactions involved. Here we show that it is possible to control the mechanical properties of hydrogels using de novo designed coiled coil peptides with different affinities for dimerization. Four different non-orthogonal peptides, designed to fold i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 41 publications
1
44
0
2
Order By: Relevance
“…These stiffness values are in the region of many soft tissues and compare well to those from previously published peptide–polymer hybrid hydrogel systems. 2022,3134 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These stiffness values are in the region of many soft tissues and compare well to those from previously published peptide–polymer hybrid hydrogel systems. 2022,3134 …”
Section: Resultsmentioning
confidence: 99%
“…One way to approach this engineering problem would be to develop a scaffold that can self-heal, providing a recovery in mechanical properties following an exposure to large strains. In previous work, peptides designed to guide the organization of polymer networks through peptide self-assembly have included coiled-coils 2022 and β-sheets. 2325 Specifically the self-assembly of β-sheets motifs have been utilized in block copolymers 2628 as nanofiber-forming grafts to synthetic polymer networks 29,30 and as cross-links in hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…As the crosslink, we used a synthetic coiled coil (CC; Figure 1). CCs are self-assembled superhelical structures (Lupas, 1996;Woolfson, 2005) have further evolved into tunable protein-based building blocks for synthetic biology and materials science where they find application in protein origami structures (Fletcher et al, 2013;Ljubetič et al, 2017) and as crosslinks for polymeric materials (Petka et al, 1998;Wang et al, 1999;Yang et al, 2006;Shen et al, 2007;Dånmark et al, 2016;Tunn et al, 2018;Tunn et al, 2019). Based on their natural abundance in biological materials and their generally established application as molecular building blocks, we consider CCs to be excellent tunable crosslinks for biomimetic material design.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made towards functional hydrogels in order to extend their mechanical strength and self‐repair properties via the addition of fillers or adhesives . The self‐healing hydrogels follow various types of mechanisms, such as hydrogen bonding, ionic interactions, host–guest interactions, crystallization, π – π interactions and multiple intermolecular interactions, which are involved in crack repair and re‐formation of their network structures …”
Section: Introductionmentioning
confidence: 99%
“…9,10 The self-healing hydrogels follow various types of mechanisms, such as hydrogen bonding, ionic interactions, host-guest interactions, crystallization, -interactions and multiple intermolecular interactions, which are involved in crack repair and re-formation of their network structures. [11][12][13][14][15][16][17][18] Poly(acrylic acid) (PAA) is a hydrophilic and superabsorbent polymer which is frequently used in various applications, especially in drug delivery due to the presence of carboxyl groups which induce hydrophilicity, ionic character and pH responsiveness. Several studies have been reported regarding the use of PAA gels in self-healing applications by exploiting the carboxyl functionality which mediates hydrogen bonding across a damaged hydrogel.…”
Section: Introductionmentioning
confidence: 99%